2004
DOI: 10.1002/uog.1756
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional power Doppler imaging of early‐stage cervical cancer

Abstract: Objectives To characterize intratumoral vascularization in early-stage cervical cancer by three-dimensional (3D) power Doppler ultrasound.Methods One hundred and forty-one patients with carcinoma of the uterine cervix and 30 normal controls were studied by transvaginal 3D power Doppler ultrasound. The tumor volume of the cervical cancer was determined. VI, FI and VFI: localized, peripheral, scattered and single-vessel The blood flow within the tumor or normal cervix was measured and expressed as the vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
3
27
0
3
Order By: Relevance
“…VI, FI and VFI were significantly higher in patients with cancer than in normal controls. This finding is in agreement with those reported by other investigators, .…”
Section: Discussionsupporting
confidence: 94%
“…VI, FI and VFI were significantly higher in patients with cancer than in normal controls. This finding is in agreement with those reported by other investigators, .…”
Section: Discussionsupporting
confidence: 94%
“…The other study was published by Hsu et al 21 These authors analyzed 97 women with early-stage cervical cancer. They found that 3D-PDA indexes were significantly higher in patients with detectable tumors compared with those in patients without detectable tumors (mostly because of prior conization) or in healthy women used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hsu et al has reported the results of applying 3D Power Doppler in 141 patients with early stage cervical cancer. They found blood flow in 85 % of the tumors and tumor vascularization was correlated with tumor volume [32]. On the other hand, Alcazar et al [33], Tanaka and Umesaki [34], and Belitsos et al [35] did find that tumor vascularization as assessed by 3D power ultrasound correlated with some tumor characteristics such as tumor stage and histologic grade.…”
Section: Transvaginal Color Doppler In Cervical Cancermentioning
confidence: 94%